INFLUENCE OF PROJECT MACRO PLANNING PROCESS ON PERFORMANCE OF GATED COMMUNITY HOUSING PROJECTS IN NAIROBI COUNTY, KENYA - Musyoka, Michael Chris; Gakuu, Prof. Christopher; Kyalo, Dr. Dorothy Ndunge (IJRDO - Journal of Applied Management Science, 2017)
The principal objective of this was to examine the influence of project macro planning process on performance of gated community housing projects in Nairobi County, Kenya. The study population comprised of all active gated community housing projects initiated in 2009 – 2014. A total of 572 respondents were drawn from 143 sampled gated community housing projects from the seventeen sub-counties of Nairobi County using census, stratified, simple random, and purposive sampling techniques. A standardized open ended interview guide and a questionnaire with both open and closed-ended items were used to collect data. Descriptive statistics showed that projects macro planning process had an influence on performance of gated community housing construction projects.The value of r 2 was 0.429, indicating that project macro planning process explained42.9% of the variation in the performance in gated community housing projects in Nairobi County, Kenya. The β coefficient was 0.655, indicating that project macro planning process had statistically significant influence on the performance of gated community housing projects (β=0.655, t=10.962, p=0.000<0.05). The β value implied that every unit change on the performance of gated community housing projects is associated with 65.5% changes in project macro planning process.